2015
DOI: 10.1002/pssa.201532256
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐supported AuPt and AuPd bimetallic nanocomposites as formic acid electrooxidation catalysts

Abstract: Repetitive syntheses of six AuPt/Vulcan carbon (VC) and six AuPd/VC nanocomposites by NaBH4 solution reduction of equimolar mixtures of HAuCl4 · xH2O and H2PtCl6 · 6H2O salts or HAuCl4 · xH2O and Na2PdCl4 salts gives nanocomposites having highly dispersed metal alloy nanoparticles of similar average size (4–7 ± 2 nm). Significant variation in nanocomposite physical and electrochemical properties is observed. AuM alloy stoichiometries and total metal wt% vary by as much as ±11 at% and ±5 wt%, respectively. Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Bimetallic alloy surfaces have attracted considerable attention for improvement of the activity and/or the selectivity of metallic catalysts because of the possibility to tune the geometric and surface electronic structures that are particularly important in determining chemical reactions . In particular, nickel‐based alloys have been found to be good catalysts for diverse reactions including aqueous‐phase reforming of oxygenated hydrocarbons , the synthesis gas reactions , propane reforming , and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic alloy surfaces have attracted considerable attention for improvement of the activity and/or the selectivity of metallic catalysts because of the possibility to tune the geometric and surface electronic structures that are particularly important in determining chemical reactions . In particular, nickel‐based alloys have been found to be good catalysts for diverse reactions including aqueous‐phase reforming of oxygenated hydrocarbons , the synthesis gas reactions , propane reforming , and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the excellent catalytic activities reported for the above-mentioned bimetallic systems, Pd based nanoparticles have undoubtedly exhibited the best overall catalytic performance for the hydrogenation of 4-NP [24]. Previous studies showed that Pd-based bimetallic NPs are more effective than Pt-Au bimetallic NPs [25][26][27][28][29]. Alloying of Au-Pd results in modifying electronic and surface properties and in turn the adsorption and activation for substrates and thus yielding relatively faster reaction rate constants compared to Au-Pt alloys [25].…”
Section: Phil Trans R Soc Amentioning
confidence: 99%
“…Nanocomposites, especially functional metal oxide supported transition metal, have attracted intensive research attention in recent years [1][2][3][4][5] . The hybrid systems that consist of two or more components usually exhibit special synergic functionalities and novel optoelectronic, magnetic and catalytic properties over their individual counterparts, making them good candidates in a wide range of application areas, such as biology, solar cells, catalysis and optoelectronic devices [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%